Identifikasi jamur (Malassezia furfur) pada kulit wanita penderita pityriasis versicolor penghuni Lembaga Permasyarakatan Perempuan Kelas II A Sungguminasa - Marlita, Sri; Hartati; Taufiq, Nuramaniyah (Program Studi Teknologi Laboratorium Medis, 2024)
Malassezia fufur is normal flora on the skin and will turn into a pathogen under certain conditions that support fungal growth, such as poor personal hygiene, in addition to environmental factor such as high temperature aand humidity, sweat gland production, and malnutrition. The Malasszia furfur causes pityriasis Versicolor. The aim of this research was to identify the Malassezia furfur in inmates of class II A Women’s Prison Sungguminasa. Thisresearch was conducted at the Microbiology Laboratori, Faculty of Medicine, Hasanuddin University. The samples were taken at Class II A Women’s Prison Sungguminasa. Samples were taken from 10 respondents in the from of skin swabs suffering from Pityriasis Versicolor, then inoculated on SDA media which had been added with chloramphenicol and the incubated at 37oC for 7 days. Based on macroscopic obsevations, colonies had the characteristics of the Malassezia furfur. Determining microscopic morphology, colony preparation were made with Lactophenol catton blue staining and then observed under a microscope with 40 time magnification . The research result showed that no prison were infected with the Malassezia furfur.